FGF21: An Emerging Therapeutic Target for Non-Alcoholic Steatohepatitis and Related Metabolic Diseases - Tillman, Erik J.; Rolph, Tim (Frontiers in Endocrinology, 2020)
The rising global prevalence of obesity, metabolic syndrome, and type 2 diabetes has driven a sharp increase in non-alcoholic fatty liver disease (NAFLD), characterized by excessive fat accumulation in the liver. Approximately one-sixth of the NAFLD population progresses to non-alcoholic steatohepatitis (NASH) with liver inflammation, hepatocyte injury and cell death, liver fibrosis and cirrhosis. NASH is one of the leading causes of liver transplant, and an increasingly common cause of hepatocellular carcinoma (HCC), underscoring the need for intervention. The complex pathophysiology of NASH, and a predicted prevalence of 3–5% of the adult population worldwide, has prompted drug development programs aimed at multiple targets across all stages of the disease. Currently, there are no approved therapeutics. Liver-related morbidity and mortality are highest in more advanced fibrotic NASH, which has led to an early focus on anti-fibrotic approaches to prevent progression to cirrhosis and HCC. Due to limited clinical efficacy, anti-fibrotic approaches have been superseded by mechanisms that target the underlying driver of NASH pathogenesis, namely steatosis, which drives hepatocyte injury and downstream inflammation and fibrosis. Among this wave of therapeutic mechanisms targeting the underlying pathogenesis of NASH, the hormone fibroblast growth factor 21 (FGF21) holds considerable promise; it decreases liver fat and hepatocyte injury while suppressing inflammation and fibrosis across multiple preclinical studies. In this review, we summarize preclinical and clinical data from studies with FGF21 and FGF21 analogs, in the context of the pathophysiology of NASH and underlying metabolic diseases.